Mortality of COVID-19 pneumonia during anticancer treatment in lung cancer patients - Bursać Daliborka; Zarić Bojan; Bokan Darijo; Kovačević Tomi; Stojšić Vladimir; Petkov Svetlana; Mitrović Kosana; Stojanović Goran (Vojnosanitetski Pregled)
Background/Aim. The coronavirus disease 2019 (COVID-19) pandemic has multiple impacts on the management of cancer patients. Treatment of malignancies, including chemotherapy, targeted therapy, immunotherapy, and radiotherapy, can suppress the immune system and lead to the development of severe complications of COVID-19. The aim of this study was to determine the mortality of lung cancer (LC) patients in whom the COVID-19 was confirmed during active antitumor treatment. Methods. This retrospective study was conducted at the Institute for Pulmonary Diseases of Vojvodina, Sremska Kamenica, Serbia. All patients included in the study underwent active anticancer treatment at the time of diagnosis of COVID-19. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection was determined by a polymerase chain reaction (PCR) test. Patient data were collected using the institutional database and the observed period was from November 20, 2020, to June 5, 2021. Statistical analysis of the derived patient data used multivariate and univariate testing. Results. Out of 828 observed COVID-19 hospitalized patients, 81 were LC patients on active antitumor treatment. Patients were predominantly male (67.9%), smokers (55.6%), and with an average age of 66.5 years (range 43–83). The majority of patients (50.6%) had the Eastern Cooperative Oncology Group Performance Status (ECOG PS) 1, and 83.9% had at least one comorbidity. The most common comorbidities were arterial hypertension (66.7%), chronic obstructive pulmonary disease (COPD) (28.4%), and diabetes mellitus (21%). Obesity, congestive heart failure, and other cardiovascular diseases were present in 11%, 6.2%, and 7.4% of patients, respectively. The most common was adenocarcinoma (33.3%), followed by squamous (30.9%) and small-cell LC (24.7%). Predominantly, 63% of the patients were in stage III of the disease, and 33.3% were in stage IV. Metastases were most commonly present in the contralateral lung/pleura (14.8%), brain (6.2%), bone (3.7%), and liver (3.7%). Systemic anticancer therapy was applied in 37 out of 81 patients (45.6%), chest radiotherapy in 35 (43.2%), concurrent chemo-radiotherapy in 1 (1.2%), and other types of radiotherapy in 8 (9.87%) patients. The most common forms of systemic therapy were chemotherapy (35.8%), immunotherapy (7.4%), and targeted therapy (2.4%). The most common chemotherapy was a cisplatin-based regiment applied in 34.6% of patients. The mortality from COVID-19 was 19.8%. The statistical significance in relation to the type of treatment was not observed. Statistical significance was observed between mortality and the ECOG PS (p = 0.011). Conclusion. LC patients are dependent on antitumor treatment and, at the same time, highly susceptible to potential infection. In this study, we did not find statistically significant differences in mortality related to the type of antitumor treatment in COVID-19 positive LC patients. Further detailed research on a larger scale is needed in order to explore the effects of SARS-CoV-2 on cancer patients. All possible methods of protection against SARS-CoV-2 virus should be performed in order to minimize the risk of infection in all but especially in immunocompromised cancer patients.